Acute care and perioperative point-of-care ultrasound - Ramsingh, Davinder (Cambridge Scholars Publishing, 2021)
This book is designed to serve as an introduction into the topic of point of care ultrasound, and highlights how it can be applied to improve care in the acute care and perioperative settings. Each section is designed to be succinct and provide a brief background on the topic, a description and illustration of image acquisition, and a discussion of essential pathology identification.